(untitled) (Colombia Medica, 2019)
Objective: This study aims to carry out the cultural adaptation and the validation of the GOHAI scale for the Colombian population. Methods: Translation process, cultural adaptation, and content and face validity were carried out with a sample of 63 participants as a pretest. The validation counted with a sample of 7,200 subjects, divided into two groups: a work sample (WS) with 3,628 subjects and a confirmatory sample (CS) with 3,572 subjects. Construct, criterion validity and internal consistency were performed for both samples. Test-retest reliability was assessed with a sub-sample of 75 participants Results: The GOHAI showed an appropriate face and content validity, the pre-test revealed an understandable questionnaire, the scale showed a unidimensional factorial structure and a Cronbach’s Alpha of 0.8. Convergent validity with a self-perception on general health scale pointed to a significant correlation (p= 0.0001), while discriminant validity showed significant differences regarding groups according to age group, skin color, educational level, socio-economic level, healthcare affiliation and self-perception about need of dental prostheses. Gender groups did not show significant differences among groups within either sample. The CS showed similar results, differences existed among factorial structures of 2 and 3 factors, and for discriminant validity, the CS showed statistically significant differences for the Area variable not in the WS. Kendall’s test-retest analysis’s correlation is 0.85 (p= 0.0000). Conclusion: The GOHAI scale is valid and reliable enough to be used as a measure of OralHealth-Related Quality of Life in the Colombian elderly population, also could be applied for other Latin-American populations.